Analisis Kualitas E-learning Lembaga Pendidikan Terpadu Nurul Ilmi Banyuasin Menggunakan Metode Webqual 4.0 - Muhammad Kresna; Nia Oktaviani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
E-learning has a very important role to advance the world of education, because with E-learning it can help teaching and learning activities. One of the schools in the city of Palembang Integrated Education Institute Nurul Ilmi Banyuasin has been using website-based E-learning since 2020, which functions as an online learning medium. This research uses the Webqual 4.0 method which consists of (usability quality, information quality, service interaction and visuals). quality). The problem in this study is that the Nurul Ilmi Banyuasin Integrated Education Institute does not yet know the level of quality of E-learning services. Therefore in this study an analysis will be carried out to measure the extent to which the quality level of E-Learning at the Nurul Ilmi Banyuasin Integrated Education Institute. it is not yet known the level of quality of E-learning services. Therefore, in this study an analysis will be carried out to measure the extent to which the quality level of E-Learning at the Nurul Ilmi Banyuasin Integrated Education Institute. There are several things that affect the level of user satisfaction with the E-Learning system, including using e-learning and web quality which will affect the level of user satisfaction. The higher the quality of a web, the more users will access the web. User involvement in the use of E-Learning technology will determine the success of a quality system and information. The quality of information that is in accordance with what is needed will provide satisfaction for the user. This study is expected to describe the relationship between user perceptions of the measurement of E-learning services at the Nurul Ilmi Integrated Education Institute to improve or complete the information in the E-learning.